Increased Serum Sialic Acids in Depression. - Abdul Hussein, Hussein Kadhem; Isa, Saadoon A.; Al-Shamma, Ghassan A. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Total serum sialic acid (TSA) and lipid associated sialic acid (LSA) have not been measured yet in depressive disorders.Aim :The present study was undertaken to show if there is any change in the concentration of different forms of sialic acids in patients with depressive disorder.Methods: TSA and LSA levels have been estimated in serum of 72 patients with depression, in addition to 50 healthy controls .Results reflect a significant increase (p